MTOR inhibition decreases SOX2-SOX9 mediated glioma stem cell activity and temozolomide resistance. (2nd April 2016) - Garros-Regulez, Laura; Aldaz, Paula; Arrizabalaga, Olatz; Moncho-Amor, Veronica; Carrasco-Garcia, Estefania; Manterola, Lorea; Moreno-Cugnon, Leire; Barrena, Cristina; Villanua, Jorge; Ruiz, Irune; Pollard, Steven; Lovell-Badge, Robin; et al.
ABSTRACT: Background : SOX2 and SOX9 are commonly overexpressed in glioblastoma, and regulate the activity of glioma stem cells (GSCs). Their specific and overlapping roles in GSCs and glioma treatment remain unclear. Methods : SOX2 and SOX9 levels were examined in human biopsies. Gain and loss of function determined the impact of altering SOX2 and SOX9 on cell proliferation, senescence, stem cell activity, tumorigenesis and chemoresistance. Results : SOX2 and SOX9 expression correlates positively in glioma cells and glioblastoma biopsies. High levels of SOX2 bypass cellular senescence and promote resistance to temozolomide. Mechanistic investigations revealed that SOX2 acts upstream of SOX9. mTOR genetic and pharmacologic (rapamycin) inhibition decreased SOX2 and SOX9 expression, and reversed chemoresistance. Conclusions : Our findings reveal SOX2-SOX9 as an oncogenic axis that regulates stem cell properties and chemoresistance. We identify that rapamycin abrogate SOX protein expression and provide evidence that a combination of rapamycin and temozolomide inhibits tumor growth in cells with high SOX2/SOX9.